2017
DOI: 10.1108/ijopm-01-2016-0053
|View full text |Cite
|
Sign up to set email alerts
|

Quality ambidexterity, competitive strategies, and financial performance

Abstract: Purpose -The purpose of this paper is to examine the relationship between quality ambidexterity, competitive strategies (cost leadership, differentiation, and focus), and firm performance in Palestinian industry, and to analyze the combination of quality exploitation and quality exploration (quality ambidexterity) associated with different levels of each competitive strategy. Design/methodology/approach -Using data collected through a survey of 205Palestinian industrial firms, the study conducted Structural Eq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 65 publications
3
30
0
2
Order By: Relevance
“… There is a positive and significant effect of ambidexterity on firm performance in traditional market MSMEs in Sleman Regency. The results of the study are supported by previous research conducted by Kedzierska (2018), Comez (2016), Tomljenović & Stilin (2010), Herzallah, Gutierrez, & Rosas (2017), Almahendra & Budiarto (2017), Torres, Roehrich, & Lewis (2017) and Luu (2017) who also stated that ambidexterity has a positive influence on firm performance.  There is a positive but not significant influence between strategy orientation and firm performance in traditional market MSMEs in Sleman Regency.…”
Section: Discussionsupporting
confidence: 85%
“… There is a positive and significant effect of ambidexterity on firm performance in traditional market MSMEs in Sleman Regency. The results of the study are supported by previous research conducted by Kedzierska (2018), Comez (2016), Tomljenović & Stilin (2010), Herzallah, Gutierrez, & Rosas (2017), Almahendra & Budiarto (2017), Torres, Roehrich, & Lewis (2017) and Luu (2017) who also stated that ambidexterity has a positive influence on firm performance.  There is a positive but not significant influence between strategy orientation and firm performance in traditional market MSMEs in Sleman Regency.…”
Section: Discussionsupporting
confidence: 85%
“…Third, by studying the performance impact of QM practices conditionally on a firm's competitive strategy focus, we contribute to closing a gap in the research landscape about the contingent impact of QM practices (Nair, 2006). Fourth, we add clarity to the conceptual associations between competitive strategy and QM practices and advance this emerging stream of research (Herzallah et al, 2017).…”
Section: Implications For Theorymentioning
confidence: 98%
“…We will argue later that some firms can profit more from attributing attention to both QM practices than others when outlining our contingency hypotheses. Still, we posit that, at the core, the interplay between both exploitative and explorative QM practices has a positive impact on a firm's performance and longevity (Kim and Huh, 2015;Piao, 2014;Herzallah et al, 2017), and put forward the following hypothesis:…”
Section: Hypotheses On the Impact Of Exploitative And Explorative Qm Practices On Performancementioning
confidence: 99%
“…Based on their study of 231 Spanish manufacturing companies, they also found that higher environmental dynamism strengthened this effect and thus echoing the results of Frank, Güttel [18] where higher environmental dynamism increased the importance of ambidextrous capabilities. Others including Herzallah, Gutierrez-Gutierrez [19] linked what they labelled as "quality ambidexterity" to strategic intentconcluding that ambidextrous capabilities had a positive relationship on cost leadership, differentiation and focus organisational strategies (though focus had a negative relationship on manufacturing performance).…”
Section: Ambidexterity and Operations Management Practicesmentioning
confidence: 99%